Clinical Holistic Medicine: Classic Art of Healingor the Therapeutic Touch - Søren Ventegodt; Mohammed Morad; Joav Merrick (The Scientific World Journal)
Touching is often a forgotten part of medicine. The manual medicine or therapeutic touch (TT) is much more powerful than many modern, biomedically oriented physicians think. Pain and discomfort can be alleviated just by touching the sick area and in this way help the patient to be in better contact with the tissue and organs of their body. Lack of presence in the body seems to be connected with many symptoms that can be readily reversed simply by sensitive touch. When touch is combined with therapeutic work on mind and feelings, holistic healing seems to be facilitated and many problems can be solved in a direct and easy way in the clinic without drugs. This paper gives examples of the strength of manual medicine or therapeutic touch in its most simple form, and points to the power of physical contact between physician and his patient in the context of the theory and practice of holistic healing. Intimacy seems highly beneficial for the process of healing and it is very important to distinguish clearly between intimacy and sexuality for the physician and his patent to be able to give and receive touch without fear and without holding back emotionally.